Divestment Activities of Companies in Volatile Times - Karol WOJTOWICZ; Konrad SZYDŁOWSKI (Communications of International Proceedings, 2025)
The main objective of the research is to evaluate how the divestment activities of selected companies in the fuel sector have been affected by the impact of the ongoing pandemic and the war in Ukraine. The study focused on a group of eight oil companies, covering the period from January 2018 to December 2022. The study analyzed both companies’ divestment indicators and their financial condition, including profitability, liquidity, leverage. The findings reveal that adverse economic conditions did not constitute a major driver of divestment activity. This was particularly evident in 2020, when the COVID-19 pandemic negatively impacted companies’ financial positions. Throughout this period, divestment activity remained lower compared to years characterized by more favorable economic conditions. The analysis further highlighted that divestments can represent a valuable source of financing for corporate operations and contribute to enhancing financial liquidity. However, the considerable irregularity of proceeds from asset sales suggests that divestments may serve primarily as a supplementary means of raising capital. JEL codes: G15, G31, E32.
Keywords: divestments; oil companies; COVID-19 pandemic.